Stanovanjske soseske v Katmanduju - Shrestha, Bijaya K. (Urbani izziv, 2013)
Residential neighbourhoods developed using various techniques in Kathmandu by both the public and private sectors have not only provided a poor urban setting and failed to address socio-cultural needs, but are also poor at building a community and creating links to the built environment, with the result that the planned areas lack a sense of place and the inhabitants lack afeeling of home. Although traditional neighbourhoods in the historic core area had many features of a good residential neighbourhood in the past, they are currently undergoing rapid destruction. The residents of these neighbourhoods have little awareness of these issues. The existing legal and institutional frameworks are inadequate and ineffective and cannot address these problems, and so the formulation of design guidelines, their strict implementation, and enhancement of socio-cultural events including social networking are recommended for future residential neighbourhood development.
Keywords: bivalno okolje; ekonomika; Kathmandu; Katmandu; Nepal; prostorsko urejanje; stanovanja; stanovanjska naselja